DEALING WITH TRAUMATIC EXPERIENCES OCCURRING AS A CONSEQUENCE OF DISAPPEARANCE: (Nights When We Fell Asleep In Pompeii by Davor Stojanovski) (Philological Studies, 2024)
In this paper, we dwell on the interpretation of trauma through the dominant Western model of cultural trauma which relies heavily on the Freudian conceptualization of trauma and its psychological consequences. This includes the traumatized subject's inability to articulate their trauma, raising of the question of trauma's delay by focusing primarily on the gap between traumatic experience and artistic expression. The consequences left by trauma are practically expolored through the analysis of the novel The Night We Slept In Pompeii by the Macedonian author Davor Stojanovski, with several segments taken as reference points. The central point of the analysis is the disappearance of the two main characters around whose absence the entire action of the novel is woven. Narratives of trauma are often called narratives of indirection, in which textual indeterminacy is indexical to an absent, traumatic referent. The indirectness in the narrative procedure is indicated by the focus on another event (the traffic accident), but also the title of the novel itself with the mention of the ancient city of Pompeii, to which the various associations of the readers are connected. They are given the active task of filling in the textual gaps according to their own reasoning. The underdeveloped historical analogy in this novel is only the author's initial attempt to show that a non-linear or fragmented way of storytelling can mimic symptoms of trauma on a formal level, such as silence and repetitive images characteristic of post-traumatic stress. The silence of the protagonist Sarah is used to develop the story in two directions: in the repeated suspicious and aggressive experiences and behaviors of the second narrator (the mother Kaya) that change her entire life and in the impossibility of discovering the mystery that is carried by Mrs. Novitska (the aged Sarah) as the third narrator in the novel.The idea that a novel can contain something unspoken, something that cannot be easily named, but which emerges through it in a complex way, underlies the theoretical elaboration of this paper. The author Stojanovski not only approaches the challenges of transmitting trauma only in terms of the limits of language or narration, but through this novel he also points out other reasons for the occurrence of trauma such as the imperfection of modern society, the process of growing up and the relationship between parents and children. It is precisely the emotional sufferings of the parents of the missing protagonists that constitute the narrative structure of the entire novel. That is why our analysis relies on the following segments: anticipation, faith, fear, aggressiveness, sadness, pain and moral dilemmas felt by the parents of the disappeared.